2009
DOI: 10.1111/j.1749-6632.2009.04093.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gravity on Transpiration of Plant Leaves

Abstract: To clarify effects of gravity on the water vapor exchange between plants and the ambient air, we evaluated the transpiration rate of plant leaves at 0.01, 1.0, and 2.0 g for 20 s each during parabolic airplane flights. The transpiration rates of a strawberry leaf and a replica leaf made of wet cloth were determined using a chamber method with humidity sensors. Absolute humidity at 3 and 8 mm below the lower surface of leaves was measured to evaluate the effect of gravity on humidity near leaves and estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Among these environmental changes, the effects of gravity on land may undoubtedly have induced alterations in the physiology, anatomy, and growth of bryophytes, extrapolated from previous findings obtained from vascular plants. Gravity influences the physiological processes of vascular plants including long-distance water transport (Lambers et al 2008 ), leaf gas exchange (Hirai and Kitaya 2009 ), cell proliferation (Matía et al 2010 ), and cell wall rigidity (Hoson and Wakabayashi 2015 ) and, thus, plant growth (Hangarter 1997 ). Nevertheless, few studies have investigated the gravitational responses of bryophytes even though gravitropism has been extensively examined (Banbury 1962 ; Cove and Quatrano 2006 ; Martin et al 2009 ; Repp et al 2004 ; Schwuchow et al 2002 ); only one study showed the significant effect of microgravity on the growth pattern of the dark-grown protonemata of the moss Ceratodon purpureus (Kern et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these environmental changes, the effects of gravity on land may undoubtedly have induced alterations in the physiology, anatomy, and growth of bryophytes, extrapolated from previous findings obtained from vascular plants. Gravity influences the physiological processes of vascular plants including long-distance water transport (Lambers et al 2008 ), leaf gas exchange (Hirai and Kitaya 2009 ), cell proliferation (Matía et al 2010 ), and cell wall rigidity (Hoson and Wakabayashi 2015 ) and, thus, plant growth (Hangarter 1997 ). Nevertheless, few studies have investigated the gravitational responses of bryophytes even though gravitropism has been extensively examined (Banbury 1962 ; Cove and Quatrano 2006 ; Martin et al 2009 ; Repp et al 2004 ; Schwuchow et al 2002 ); only one study showed the significant effect of microgravity on the growth pattern of the dark-grown protonemata of the moss Ceratodon purpureus (Kern et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…7,8) Plant stem sap flow is an important indicator of plant growth because water and nutrients are transported from the roots to the leaves through the stems by transpiration. In one of our previous studies, transpiration was suppressed under microgravity (0.01 g) conditions without forced air circulation; 9,10) in another, stem sap flow was suppressed in parabolic airplane flights. 11) It is generally presumed that closed plant culture facilities will be used for space farming.…”
Section: Introductionmentioning
confidence: 80%
“…In a previous study without forced air movements, transpiration was suppressed at 0.01 g. [9][10][11] Limited stem sap flow is presumably caused by the suppression of transpiration in leaves. In consequence, it will lead to restricted water and nutrient flow from the roots, thereby suppressing plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to clarify the influence of microgravity on water transport in plants to facilitate the building of structures that have adequate environmental control systems for the long-duration cultivation of healthy plants in space (Monje et al, 2003). We have previously reported that wind has a considerable and positive effect on transpiration, particularly under microgravity conditions in parabolic airplane flights (Kitaya et al, 2006;Hirai and Kitaya, 2009;Tokuda et al, 2018a). Sap flow is highly correlated with transpiration (e.g., Sakuratani, 1981;Dugas, 1990;Smith and Allen, 1996).…”
Section: Introductionmentioning
confidence: 99%